Analysis of Mathematic Communication Ability to be Reviewed From Student Learning Creativity In Statistical Materials - Budi, Samuel; Darmawan, Handi; Saputro, Marhadi (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This study aims to determine the extent of mathematical communication skills of students who have high learning creativity in statistics material in Class VIII of SMP Negeri 01 Putussibau, which are categorized in high, medium, and low learning creativity. The problem in this study is "how the analysis of mathematical communication skills in terms of student learning creativity in statistics material in Class VIII SMP Negeri 01 Putussibau", where the specific problems include: How is the mathematical communication skills of students who have high, medium, and creative learning creativity low in statistical material in Class VIII of SMP Negeri 01 Putussibau ?. This study uses descriptive research methods in the form of surveys, which are studies that only describe situations and behavior by making direct observations on objects that are sources of data. The research sample was class VIII F students, amounting to 33 students. Data collection techniques in the form of indirect communication, measurement, and data collection tools in the form of questionnaires for creativity, tests, and direct interviews. Data analysis techniques include data reduction and data presentation. Based on the description of the data obtained that the analysis of mathematical communication skills in terms of student learning creativity on statistical material. Students with high ability can work on problems well and creatively using formulas or how to solve them, students with medium ability can work on problems well, but are less creative using formulas and how to solve them, and students with low ability can already work on problems quite well, but these students have not been creative in using workmanship formulas or how to find answers to the questions given.